1997
DOI: 10.1017/s0022336000039470
|View full text |Cite
|
Sign up to set email alerts
|

Streptognathodus (Conodonta) succession at the proposed Carboniferous-Permian boundary stratotype section, Aidaralash Creek, Northern Kazakhstan

Abstract: Streptognathodus Pa elements dominate conodont faunas from the proposed Carboniferous-Permian boundary stratotype at Aidaralash Creek, northern Kazakhstan. The phyletic development of this genus provides the means for subdividing the late Gzhelian to early Sakmarian prodeltaic section (Beds 9-37) into six zones. The preferred Global Stratotype Section and Point (GSSP) for the base of the Permian System is 27 m above the base of Bed 19 at the first occurrence of Streptognathodus isolatus Chernykh, Ritter, and W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 5 publications
0
18
0
1
Order By: Relevance
“…Asselian to Sakmarian conodonts (S. constrictus) were discovered from the lowermost part of the study section (sample no. SKW11) which have been reported from Southern Ural and South China (Chernykh and Reshetkova, 1986;Chernykh and Ritter, 1997;Wang, 1994). This suggested that the age of the lowermost part of the study section is Asselian (lowermost Permian).…”
Section: Radiolarian Faunasmentioning
confidence: 79%
See 1 more Smart Citation
“…Asselian to Sakmarian conodonts (S. constrictus) were discovered from the lowermost part of the study section (sample no. SKW11) which have been reported from Southern Ural and South China (Chernykh and Reshetkova, 1986;Chernykh and Ritter, 1997;Wang, 1994). This suggested that the age of the lowermost part of the study section is Asselian (lowermost Permian).…”
Section: Radiolarian Faunasmentioning
confidence: 79%
“…sp. Among these conodont species, S. constrictus is restricted to the Asselian to Sakmarian of the Southern Urals (Chernykh and Reshetkova, 1986;Chernykh and Ritter, 1997) and South China (Wang, 1994). S. elegantulus was reported from North Thailand by Igo (1974), and is thus Late Carboniferous in age, according to the new definition for the base of the Permian (Jin et al, 1997).…”
Section: Conodonts and Siliceous Sponge Spiculesmentioning
confidence: 99%
“…The fusulinid assemblages are correlated with the Sphaeroschwagerina Biozone of Asselian-Sakmarian age in South China (Jin and Shang, 2000). Among the conodonts, some specimens assigned to Streptognathodus wabaunsensis have been redetermined as Streptognathodus isolatus (Wang, 2000) which defines the Carboniferous-Permian boundary in the Global Boundary Stratotype (Chernykh and Ritter, 1997). Thus, the Clatratus Biozone is most likely to be of the Asselian-Sakmarian age.…”
Section: Palynological Correlation and Agementioning
confidence: 99%
“…Due to the robust biostratigraphic control (e.g., Thompson, 1954;Ross, 1988, 1995;Ritter, 1995;Chernykh and Ritter, 1997) and minimal tectonic influence (West et al, 1997;Mazzullo, 1999), the U.S. Midcontinent section is ideal for studying PPT sea level change. In many of the other areas described below (except the Russian Platform), the Pennsylvanian-Permian boundary is an easily identifiable unconformity.…”
Section: United States Midcontinentmentioning
confidence: 99%
“…3). The GSSP conodont marker, Streptognathodus isolatus, has been observed in the base of the Bennett Shale (Ritter, 1995;Chernykh and Ritter, 1997) and the Nealian fusulinid fauna (described above) occurs in the Neva Limestone (Thompson, 1954).…”
Section: A21 United States Midcontinentmentioning
confidence: 99%